Cepharanthine Attenuates Early Brain Injury after Subarachnoid Hemorrhage in Mice via Inhibiting 15-Lipoxygenase-1-Mediated Microglia and Endothelial Cell Ferroptosis. (9th February 2022) - Gao, Shiqi; Zhou, Liuzhi; Lu, Jianan; Fang, Yuanjian; Wu, Haijian; Xu, Weilin; Pan, Yuanbo; Wang, Junjie; Wang, Xiaoyu; Zhang, Jianmin; Shao, Anwen
Abstract : Background . Ferroptosis is a newly identified form of programmed cell death caused by iron-dependent lipid peroxidation. Our study was designed to determine the expression patterns and role of 15-lipoxygenase-1 (ALOX15) in subarachnoid hemorrhage (SAH) and to investigate whether cepharanthine (CEP) can inhibit ferroptosis by inhibiting ALOX15 in specific cell types. Methods . A mouse model of SAH was developed by the endovascular perforation method. bEend.3 endothelial cells and BV2 microglial cells as well as RSL3 and hemin were used to simulate SAH in vitro . Mice and cell lines were treated with CEP and a group of specific oxygenase inhibitors to explore the protection effect from ferroptosis. Lipid peroxidation staining with BODIPY 581/591 C11 and transmission electron microscopy were used to identify ferroptosis in vitro and in vivo . Results . In the present study, the accumulation of lipid peroxide, a defect in the glutathione peroxidase 4 (GPx4)/glutathione (GSH) antioxidant system, highly expressed ALOX15 in microglia and endothelium, and ferroptotic changes in microglial mitochondria confirmed the occurrence of ferroptosis after SAH in vivo . Further, CEP was shown to inhibit ferroptosis and improve neurological function by downregulating the expression of ALOX15. During in vitro experiments, we investigated the important role ALOX15 in RSL3-induced endothelial ferroptosis. In addition, we found that M2-type microglia are more sensitive to RSL3-induced ferroptosis than M1-type microglia and that hemin probably induced ferroptosis in M2-type microglia by increasing ALOX15 levels and decreasing GPx4 levels. The effect of CEP treatment was also demonstrated in vitro . Conclusions . In summary, to the best of our knowledge, this is the first study demonstrating that ferroptosis occurred in the microglia and endothelium after SAH, and this process was facilitated by increased ALOX15 levels. More importantly, treatment with CEP could inhibit ferroptosis through downregulating the expression of ALOX15.